Feasibility Study of 3P Implementation in Handling Solid Waste by Empowering Housewives - Marniati Marniati; Enda Silvia Putri; Itza Mulyani; Teuku muliadi; Khairunnas Khairunnas; Cokorda Istri Dharmayant; Nur Nadiah (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2021)
The empowerment of homemakers has a significant effect on the Implementation of Extermination Transport Collection in handling solid waste to improve the cleanliness of the residential environment. The problem in this study is the low Implementation of 3P, where garbage collection is not left correctly scattered; the Transportation of garbage is not routine every day so that the garbage is scattered. Garbage is not destroyed as often as possible so that it harms health. This study aims to assess the feasibility of implementing 3P in dealing with solid waste by empowering homemakers in Drien Rampak Village, Johan Pahlawan District, West Aceh Regency. This research is a sectional observational study with one group pretest post-test design. I conducted in October 2020, which became the population of housewives with a total sample of 45 people. The study results show differences before and after measuring the 3P Implementation with the empowerment of homemakers in improving the cleanliness of the residential environment, as evidenced by the value (Probability 0.000) where there is a difference before and after measurement with a mean value of -1.622. The 3P Implementation by empowering homemakers is feasible. Suggestions for continuing to empower the role of homemakers in implementing 3P solid waste to improve the quality of cleanliness in residential environments.